Global well-posedness and inviscid limits of the generalized Oldroyd type models. (February 2022) - Zhai, Xiaoping; Dan, Yuanyuan; Li, Yongsheng
Abstract: We obtain the global small solutions to the generalized Oldroyd-B model without damping on the stress tensor in R n . Our result give positive answers partially to the question proposed by Elgindi and Liu (Remark 2 in Elgindi and Liu (2015)). The proof relies heavily on the trick of transferring dissipation from u to τ, and a new commutator estimate which may be of interest for future works. Moreover, we prove a global result of inviscid limit of two dimensional Oldroyd type models in the Sobolev spaces. The convergence rate is also obtained simultaneously.